Several Aspects of the Great Vowel Shift and Middle English Lengthening in the Open Syllable - Мячинская, Э. И. (Kalbotyra, 1985)
Quantity in Middle English was based upon interrelation of vowel consonant length within the syllable (isochrony). This means that the length was positionally determined and its variation should be regarded as allophonic, and long and short vowels of similar quality should be grouped into phonemes of the type /V̆ – V̄/, /C̆ – C̄/. However the pattern was destroyed from the very beginning by the diphthongoid pronunciation acquired by M. E. ī and ū, which thus could not be grouped into phonemes with the respective short vowels. The latter became allophones of the same phonemes as ẹ̄, ọ̄ – nearest in aperture. This explains the development of ẹ̄ and ọ̄ in the Great Vowel Shift, the direction of the change being qualitative towards the short counterpart. This shows that many changes in the vowel shirt were determined by the relations existing within the M. E. vowel system.